Systemic Lupus Erythematosus 2014 (2014)
Systemic lupus erythematosus (SLE, lupus) is the prototype of systemic autoimmune disease (AD). Immune system activation in SLE is characterized by exaggerated B-cell and T-cell responses and loss of immune tolerance against selfantigens. Production and defective elimination of antibodies, circulation and tissue deposition of immune complexes, and complement and cytokine activation contribute to clinical manifestations that range from fatigue and joint pain to severe, life-threatening organ damage